Prevalence and Antibiotic Resistance Pattern of Salmonella Isolated from Caecal Contents of Exotic Chicken in Debre Zeit and Modjo, Ethiopia - Destaw Asfaw Ali; Belege Tadesse; Aragaw Ebabu (International Journal of Microbiology)
A cross-sectional study was conducted between December, 2013, and May, 2014, to determine the prevalence and antibiotic resistance feature of Salmonella isolated from broilers slaughtered in Debre Zeit and Modjo towns, Ethiopia. A total of 384 caecal content samples were collected for microbiological examination following the standard techniques and procedures outlined by the International Organization for Standardization to isolate Salmonella. The sensitivity of the isolates subjected to nine antimicrobials was tested by the Kirby–Bauer disk diffusion method. The overall prevalence of Salmonella was 14.6%, and its occurrence differ significantly by farm (p<0.05). The occurrence of the bacteria was not statistically different in the midland (15.2%) and lowland (13.3%) (p>0.05) and between males (13.5%) and females (15.6) (p>0.05). Of the 50 isolates, 48 were resistant to at least one drug. Multidrug resistance was recorded in 43 (86.0%) of the isolates. The study demonstrated considerable prevalence and high antimicrobial resistant Salmonella in exotic chicken and indicates the potential importance of chickens as source of foodborne salmonellosis and multiple antimicrobial resistance of Salmonella. Improving the hygienic practice of farms could help to reduce the occurrence of Salmonella in farms. Further studies are needed to describe the risk factors associated with the emergence of drug-resistant Salmonella in chicken.